1996
DOI: 10.1097/00043426-199605000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Treatment of Malignant Chordoma in Children

Abstract: Ifosfamide and doxorubicin were efficacious in a patient with advanced metastatic disease, producing significant disease regression. The addition of intrathecal or intraventricular therapy with hydrocortisone, ARA-C, and methotrexate was effective in controlling CNS disease due to chordoma. There was no apparent benefit from the use of actinomycin-D, cyclophosphamide and vincristine nor the combination of cisplatin and 5-fluorouracil or high-dose methotrexate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 8 publications
0
36
0
1
Order By: Relevance
“…56 Symptomatic improvement in some patients has been shown after administration of vincristine, 51,98 but this agent has failed in combination therapy with others. 31,112 Single-agent chemotherapy (carboplatin, 37 cisplatin, 37 or methotrexate 25 ) has been found to be ineffective in terms of tumor response and pain relief. Combination therapies that are associated with varying degrees of success include hydroxyurea with 5-fluorouracil; 5 cisplatin, vinblastine, and bleomycin with concurrent radiotherapy; 6 preoperative cyclophosphamide, vincristine, doxorubicin, and decarbazine together with radiotherapy; 62 vincristine and methotrexate with leucovorin rescue; 37 and ifosfamide and doxorubicin with intrathecal or intraventricular therapy with hydrocortisone, ara-C, and methotrexate.…”
Section: Neurosurg Focus / Volume 12 / May 2002mentioning
confidence: 99%
See 1 more Smart Citation
“…56 Symptomatic improvement in some patients has been shown after administration of vincristine, 51,98 but this agent has failed in combination therapy with others. 31,112 Single-agent chemotherapy (carboplatin, 37 cisplatin, 37 or methotrexate 25 ) has been found to be ineffective in terms of tumor response and pain relief. Combination therapies that are associated with varying degrees of success include hydroxyurea with 5-fluorouracil; 5 cisplatin, vinblastine, and bleomycin with concurrent radiotherapy; 6 preoperative cyclophosphamide, vincristine, doxorubicin, and decarbazine together with radiotherapy; 62 vincristine and methotrexate with leucovorin rescue; 37 and ifosfamide and doxorubicin with intrathecal or intraventricular therapy with hydrocortisone, ara-C, and methotrexate.…”
Section: Neurosurg Focus / Volume 12 / May 2002mentioning
confidence: 99%
“…Combination therapies that are associated with varying degrees of success include hydroxyurea with 5-fluorouracil; 5 cisplatin, vinblastine, and bleomycin with concurrent radiotherapy; 6 preoperative cyclophosphamide, vincristine, doxorubicin, and decarbazine together with radiotherapy; 62 vincristine and methotrexate with leucovorin rescue; 37 and ifosfamide and doxorubicin with intrathecal or intraventricular therapy with hydrocortisone, ara-C, and methotrexate. 112 No benefit has been reported with the combination of actinomycin-D, cyclophosphamide, and vincristine, nor with cisplatin and 5-fluorouracil or highdose methotrexate.…”
Section: Neurosurg Focus / Volume 12 / May 2002mentioning
confidence: 99%
“…However, given the static nature of the bone structures, several authors have suggested that frameless stereotactic guidance can be helpful in the case of lesions such as chordomas that extensively invade the base of the skull. 62,84 Indeed, in a number of situations we have found frameless stereotaxis to be helpful in providing intraoperative feedback regarding surgical orientation and, indirectly, extent of resection during anterior extradural approaches to cranial base lesions. 29 With further technological advancements and continuing refinements intraoperative neuroimaging and guidance will likely assume a critical role during resection of such tumors.…”
Section: Surgical Approachesmentioning
confidence: 99%
“…7,11,30,60 Polychemotherapy regimens have been administered with drugs similar to soft part sarcomas (ifosfamide, doxorubicin, etoposide), and again mainly indicated where local treatment had failed previously. Few very young children have been managed with upfront chemotherapy, due to an extensive presentation of the disease locally and/or distantly.…”
Section: Review Of Literaturementioning
confidence: 99%